Development of Criteria for Assessing Nutritional Status in Moscow Children and Adolescents Using Bioimpedance Analysis Data - S. G. Rudnev; A. E. Ivanova; E. Z. Godina; A. V. Zubko; V. I. Starodubov (Здоровье мегаполиса, 2024)
Background. Body composition assessment plays an important role in characterizing physical development, monitoring health status, diagnosing nutritional disorders, and assessing disease risks.Objective. To develop the criteria for assessing nutritional status in Moscow children and adolescents using bioimpedance analysis data.Materials and methods. The research used data from a non-clinical, cross-sectional, observational study on the body composition of children and adolescents aged 5–17 in Moscow health centers from 2010 to 2019 by the method of bioimpedance analysis. A total of 115,200 persons were assessed, including 61,430 boys and 53,770 girls. Bioimpedance measurements were taken using bioimpedance analyzers according to a standard four-electrode assessment scheme in the supine position with disposable bioadhesive ECG-electrodes placed on the patient’s wrists and ankles. The relative fat mass (RFM) was assessed using the percentage of fat mass (%FM) and the fat mass index (FMI). The criteria for assessing RFM were the cut-offs of %FM and FMI calculated based on the centiles of BMI thresholds according to the IOTF ageand sex-specific criteria. Polynomial smoothing was then applied. In the same way, the criteria for assessing the relative fat-free mass (RFFM) were derived based on the cut-offs of the fat-free mass index (FFMI).Findings. Diagnostic tables were designed to determine the RFM and RFFM in Moscow children and adolescents. The prevalence of normal weight obesity was assessed.Conclusion. The study results can be used in clinical, preventive, or sports medicine to diagnose and correct nutritional status disorders as well as to monitor physical development.